PENGEMBANGAN HUBUNGAN MENUJU RELASI ROMANTIK DALAM TA’ARUF - Kania Azzahra Wibowo; Turnomo Rahardjo; Primada Qurrota Ayun (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
The ta’aruf method as a premarital exploratory process can be chosen by Muslim individuals who want to get to know their potential spouse better through a method that is in accordance with Islamic law. In this study, individuals who carry out ta’aruf are seen as a subject who has certain thoughts and feelings in the relationship development process that is passed. The whole process of thinking by individuals gives meaning to the experience of dialogue with other individuals throughout the ta’aruf process. This study aims to understand the stages of relationship development and to understand the communication patterns formed in the experience in ta’aruf. There are two theories used in this study, namely the theory of relationship development and the theory of relational dialectics. This research is a qualitative descriptive study and uses a phenomenological approach that highlights the unique experiences that the informants have gone through. Researchers conducted in-depth interviews with the four research informants to explore the experiences of each informant. The results obtained from this study are that the stages of developing relationships in ta’aruf are a dynamic process. Relationship development is not tied to a fixed path. Interpersonal relationships in ta’aruf cover the stages of contact, involvement, intimacy, deterioration, repair, and dissolution which consist of the process of exchanging personal profiles, discussion processes, and engagement, until a decision is made to marry or not to marry. Furthermore, the pattern of communication formed in ta’aruf is determined by the background of the informant and partner, the mediator, the form and the system of communication, and the involvement of the nuclear family. Belief become a factor that influences individual decision-making to move forward or backward to a certain stage in the relationship. Confidence comes from a collection of information obtained through dialogue and dialectics which is then managed within the individual.